1985
DOI: 10.1111/j.1439-0388.1985.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic parameters for some reproduction and milk production characters of the Damascus goat

Abstract: Summary Data from 2600 kidding and 1600 adult lactations, recorded between 1972 and 1978 were utilized to estimate genetic and phenotypic parameters for litter size, litter weight and milk production (after weaning) in the Damascus breed or goat. Data were first corrected for environmental effects using least‐squares constants. Estimates of heritability from daughter‐dam regressions were around zero for litter size and litter weight, whereas those for 90‐day, 150‐day, total milk yield and days in milk after we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2
3

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(18 reference statements)
0
2
2
3
Order By: Relevance
“…Estimates of moderate repeatability suggest that successful selection for that trait is possible. Our estimates of repeatability were lower than those reported by other researchers (Montaldo et al, 1982;Constantinou et al, 1985;Ilahi et al, 1998;Bagnika and Lukaszewics, 1999 Valencia (1992) reported lower repeatability estimates for TMY and LL (0.12 and 0.00) in Mexican goats than the current investigation.…”
Section: Genetic Parameter Estimates For Lifetime Lactation Traitscontrasting
confidence: 81%
“…Estimates of moderate repeatability suggest that successful selection for that trait is possible. Our estimates of repeatability were lower than those reported by other researchers (Montaldo et al, 1982;Constantinou et al, 1985;Ilahi et al, 1998;Bagnika and Lukaszewics, 1999 Valencia (1992) reported lower repeatability estimates for TMY and LL (0.12 and 0.00) in Mexican goats than the current investigation.…”
Section: Genetic Parameter Estimates For Lifetime Lactation Traitscontrasting
confidence: 81%
“…A literatura cita valores de herdabilidade para a produção de leite entre 0,16 e 0,72 (RONNINGEN, 1965(RONNINGEN, e 1967STEINE, 1976;BOUILLON e RICORDEAU, 1976;ILOEJE et al, 1981;KENNEDY et al, 1982;SULLIVAN et al, 1986;SINGH et al, 1970;PRAKASH et al, 1971;MAVROGENIS et al, 1984;CONSTANTINOU et al, 1985).…”
Section: Herdabilidadeunclassified
“…A estimativa de herdabilidade da produção de leite total, 0,296 ± 0,079 (Tabela 1), assemelhou-se mais às encontradas em raças nativas em regiões tropicais, cujos valores estão entre 0,15 e 0,35, com média de 0,28 (SINGH et al, 1970;PRAKASH et al, 1971;CONSTANTINOU et al, 1985;MAVROGENIS et al, 1984), que as obtidas em raças especializadas em países de clima temperado, cujos valores estão entre 0,28 e 0,72 e média de 0,47 (RONNINGEN, 1965;RONNINGEN, 1967;STEINE, 1976;ILOEJE et al, 1981;KENNEDY et al, 1982;SULLIVAN et al, 1986;BOICHARD et al, 1989).…”
Section: Herdabilidadeunclassified
“…The number or traits analysed varied according to the study. Studies from Cyprus (Mavrogenis et al, 1984;Constantinou et al, 1985) were restricted to the analysis of milk yield (90-day, 150-day or total). Studies from Norway or North America dealt with milk and fat traits.…”
Section: Environmental Effectsmentioning
confidence: 99%